An overview of cdc2‐like kinase 1 (Clk1) inhibitors and their therapeutic indications. Issue 2 (19th October 2022) - ElHady, Ahmed K.; El‐Gamil, Dalia S.; Abadi, Ashraf H.; Abdel‐Halim, Mohammad; Engel, Matthias
Abstract: Over the past decade, Clk1 has been identified as a promising target for the treatment of various diseases, in which deregulated alternative splicing plays a role. First small molecules targeting Clk1 are in clinical trials for the treatment of solid cancer, where variants of oncogenic proteins derived from alternative splicing promote tumor progression. Since many infectious pathogens hi‐jack the host cell's splicing machinery to ensure efficient replication, further indications in this area are under investigation, such as Influenza A, HIV‐1 virus, and Trypanosoma infections, and more will likely be discovered in the future. In addition, Clk1 was found to contribute to the progression of Alzheimer's disease through causing an imbalance of tau splicing products. Interestingly, homozygous Clk1 knockout mice showed a rather mild phenotype, opposed to what might be expected in view of the profound role of Clk1 in alternative splicing. A major drawback of most Clk1 inhibitors is their insufficient selectivity; in particular, Dyrk kinases and haspin were frequently identified as off‐targets, besides the other Clk isoforms. Only few inhibitors were shown to be selective over Dyrk1A and haspin, whereas no Clk1 inhibitor so far achieved selectivity over the Clk4 isoform. In this review, we carefully compiled all Clk1 inhibitors from the scientific literature and summarized their structure–activity relationships (SAR). In addition, we critically discuss the available selectivity data and describe the inhibitor's efficacy in cellular models, if reported. Thus, we provide a comprehensive overview on the current state of Clk1 drug discovery and highlight the most promising chemotypes.